Cleft Palate and its management - Mohamed , Yasmin Ibrahim; Almeida, Giovanna Sales Nogueira (Seven Editora, 2024)
Cleft palate is a congenital malformation that occurs due to the incomplete process of fusion of the palatal bones during fetal development, resulting in an opening in the hard and/or soft palate. This condition has a multifactorial etiology, including genetic, environmental and mixed factors, which interfere with embryological development, with heredity accounting for 25 to 30% of cases, while 70 to 80% are of multifactorial etiology. DOI:https://doi.org/10.56238/sevened2024.025-011